Quality Control of Head Cylinder Products Using the Seven Tools Approach at PT Otomotif Indonesia - Budi Nurjaman; Aris Insan Waluya; Weni Tri Sasmi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
PT Otomotif Indonesia is a Japanese manufacturing company. Company management continues to strive to improve the quality of products produced, including cylinder heads. Quality control is something that needs to be done in a company to minimise the occurrence of defective goods. The research was conducted in the machining section of the cylinder head manufacturing process. The highest cylinder head production percentage was 0.88% in November 2023. This research aims to minimise the occurrence of defects by applying the Seven Tools method. Seven Tools is a methodology consisting of seven quality control instruments: Check Sheet, Stratification, histogram diagram, Pareto diagram, scatter diagram, control chart, and Fishbone diagram. After data processing using the seven tools method, 5 errors were identified, the biggest being pen-matching errors. The 5W+1H method was used when analysing the Fishbone diagram and making recommendations for improvement. Keywords: Quality Control, Cylinder Head, Seven Tools